Religious Moderation in Silo Baru (Case Study: Tuanku Sheikh Silo) - Mhd. Joni Marpaung; Rizka Ramadani Sam; Nuraini Ade Putri Lubis; Rina Widyasari; Ismail Husein; Nafila Zendhia Ulhaq; Khoiriah Syahfitri; Puan Salwa Afifah; Rahma Utami; M. Abdul Rizki (Pena Cendekia Insani, 2021)
The religious moderation in Silo Baru will be described in this article. The purpose of this paper is to discuss religious moderation in Silo Baru, the role of religious instructors in achieving village peace, inter-religious relations, inter-religious relationship weaknesses, challenges and opportunities for religious moderation, and indicators of religious moderation. A qualitative research method was employed. Tuanku Sheikh Silau Laut's History was used as a case study. How religious moderation evolved from time to time to the present. According to the findings of this study, religious moderation is a perspective on how to understand and apply religious teachings so that they are not excessive and do not cause conflict among Muslims and people of other faiths. Of course, differences of opinion will continue to emerge in every village. However, it does not have to cause division among fellow humans. It requires religious moderation in the form of acknowledging the existence of other parties, being tolerant, respecting differences of opinion, and not imposing one's will through violence.